2014
DOI: 10.1007/s11266-014-9492-8
|View full text |Cite
|
Sign up to set email alerts
|

Accountability in Korean NPOs: Perceptions and Strategies of NPO Leaders

Abstract: This study examines how senior managers of Korean nonprofit organizations construe their accountability environment, particularly with respect to the perceived expectations of various stakeholders. In-depth interviews were conducted with 42 nonprofit executives in Seoul and six other major Korean cities. Subsequent surveys were completed by 271 organizations. The interview results were used to construct a survey instrument to generalize the findings. The findings suggest that executives of South Korean NPOs pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 40 publications
(61 reference statements)
0
16
0
Order By: Relevance
“…Indeed, the number nearly doubled between 1988 and 2003. Outside this physical growth, these nonprofit organizations have expanded in their roles, focus areas, and relationships with the state and market (Jeong, ). These roles are continually emphasized as the demand for social welfare increases in South Korean society.…”
Section: Rsos and Csos In South Koreamentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the number nearly doubled between 1988 and 2003. Outside this physical growth, these nonprofit organizations have expanded in their roles, focus areas, and relationships with the state and market (Jeong, ). These roles are continually emphasized as the demand for social welfare increases in South Korean society.…”
Section: Rsos and Csos In South Koreamentioning
confidence: 99%
“…With service‐oriented organizations on the other, advocacy‐oriented nonprofit organizations make up one side of the dual structure involved in South Korean nonprofit organizations. These organizations have weaker engagements with governments compared to service‐oriented organizations with low levels of financial sustainability (Jeong, ).…”
Section: Rsos and Csos In South Koreamentioning
confidence: 99%
See 1 more Smart Citation
“…The multi-faceted roles of civil society in South Korean development history have been distinctive. South Korean civil society organizations haves played multiple roles as cooperative partners in a developmental state (Jeong 2015), adversarial advocates of democracy against authoritarian regimes in the context of social movements, and as professional and entrepreneurial participants in the policy process (Jeong 2013;Jeong and Kearns 2015;Kim 2006). Kim and Jung (2019) documented the chronological development of the Korean nonprofit sector, identifying three stages: a rudimentary stage ; a sophisticated stage ; and an elaborated and transformed stage (2008-present).…”
Section: Historical Review Of the Government -Civil Society Relationsmentioning
confidence: 99%
“…Furthermore, accountability and professionalization have become a significant pressure on nonprofit organizations (Betzler & Gmür, ). The research found that senior nonprofit managers in Korea recognize the roles of professionalization in establishing organizational accountability (Jeong & Kearns, ). Also, a series of scandals have raised the public attention on accountability issues in the nonprofit sector (Jeong & Kearns, ).…”
Section: Sector Switching To the Nonprofit Sectormentioning
confidence: 99%